DNA barcoding in medicinal plants: Testing the potential of a proposed barcoding marker for identification of Uncaria species from China. (June 2015) - Zhang, Zhong-Lian; Song, Mei-Fang; Guan, Yan-Hong; Li, Hai-Tao; Niu, Ying-Feng; Zhang, Li-Xia; Ma, Xiao-Jun
Abstract: DNA barcoding, an increasingly popular mean of species identification, has been widely used for global species identification despite a consensus not being reached regarding which DNA sequences can be used as the best plant barcodes. In this study, we tested the feasibility of five candidate DNA barcodes (nrITS, nrITS2, matk, rbcL and trnH-psbA ) for identifying Uncaria species. We collected a total of 54 specimens of 10 Uncaria species across its distributional range. BLAST, barcoding gaps, tree-based methods and TAXONDNA analysis were used to investigate the molecular identification capability of the candidate DNA barcodes. The results showed that the ITS2 is most suitable as a candidate DNA barcode for identification of medicinal plants of the genus Uncaria . Highlights: Screened the DNA barcode that suitable for the plant of Uncaria Evaluated the identification efficiency using methods of BLAST, barcoding gap, tree-based methods and TaxonDNA analysis. The results showed that the ITS2 is the most suitable DNA barcode for Uncaria plant.